Peran Keluarga Pada Tingkat Kemandirian Personal Hygiene Anak Tunagrahita - Tonara, Arda; Abadi Miko, Nopri; Efendi, Ashari (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2023)
The family's responsibility is to inspire, educate, and support their children so that they can be self-sufficient and meet their physical and spiritual demands. What is the function of the family at the level of personal hygiene independence for mentally challenged children at the Qalbun Insanni Private Special School, Central Aceh District, is the formulation of the problem in this study. Identifying the Family's Role at the Personal Hygiene Independence Level for Children with Mental Disability at Qalbun Insani Private Special Schools in Central Aceh District was the goal of this study. Both observation and questionnaires were employed as data gathering methods in this study. While the Likert scale is used to evaluate the data performance analysis in this study. As many as 75% of families of mentally handicapped children at the Qalbun Insanni Private Special School, Central Aceh District, claimed that the family has a role in the good category, according to the study's findings. The foundation of behavior, in this case the behavior of independent personal hygiene, is formed by parents. forms of independent personal hygiene behavior, such as the initial role of parents as a motivator by assisting children to bathe themselves, keeping cleanliness, and complimenting youngsters on their good conduct. The second is that of parents acting as educators by teaching kids how to take care of themselves in the bathroom, clean their own genitalia after urinating, defecate in the anal canal after doing so, clean their ears, eyes, and nose when there is dirt in them, brush their teeth, trim their nails, and wash their hands before and after meals. (1) To Qalbun Insanni Private SLB in Central Aceh Regency to further strengthen the independence of children with mental retardation. (2) It is anticipated that families of mentally impaired children will be able to teach their offspring how to become more independent in the future. (3) I expect that this research can be carried out by further researchers in a larger situation with more participants.